A new approach to the treatment of spinal instability: Fusion or structural reinforcement without surgery?. (November 2020) - Dang, Lei; Zhu, Jinglin; Liu, Zhongjun; Liu, Xiaoguang; Jiang, Liang; Wei, Feng; Song, Chunli
Abstract: Spinal instability related low back pain is a common condition resulting from degeneration and loss of stiffness of the intervertebral joint. In order to restore stability, highly invasive surgical fusion is needed for patients who are not responding to conservative treatment. Given the risk and complications of surgery, there has been the urge for improvement with a less invasive solution. Formation of vertebral body osteophytes is a common observation that has been treated as a degenerative condition. However, recent studies have associated it with reduced motion of spinal segments. Unlike the traditional view, we regard it as adaptive reactions aiming to repair and hypothesize that the spinal segments could be stabilized or fused by intentionally induced osteophytes growth at the mobile parts of the intervertebral joint. This could be achieved by injecting Bone Morphogenetic Proteins to the anterior ends of the vertebral bodies and/or the facet joints on both sides of two consecutive vertebrae percutaneously. If verified, it would be the first time that fusion could be achieved without surgery. Hence it would provide a valuable alternative to current treatments of spinal instability. Preliminary test in favor of this hypothesis is presented and we recommend that a formal study with sufficient number of samples is needed for verification.